Characterization of a monoclonal antibody specific for Brucella smooth lipopolysaccharide and development of a competitive enzyme-linked immunosorbent assay to improve the serological diagnosis of brucellosis. - Weynants, V (1996)
The reactivity of monoclonal antibody (MAb) 12G12 was analyzed in regard to the main biovars of Brucella species and some members of the families Enterobacteriaceae and Vibrionaceae which present serological cross-reactions with the smooth lipopolysaccharide (S-LPS) of Brucella species. This MAb was strictly directed against the common specific epitope of the Brucella S-LPS. It recognized all of the smooth Brucella strains and biovars except B. suis biovar 2. In order to improve the specificity of the serological diagnosis of brucellosis, a competitive enzyme-linked immunosorbent assay (cELISA) was developed with the horseradish peroxidase-conjugated MAbs 12G12 and S-LPS of B. melitensis Rev1. The specificity of the cELISA was analyzed with 936 serum samples from healthy cattle. The assay was evaluated with sera from heifers (n = 18) experimentally infected with B. abortus 544. After infection, the performance of the cELISA was in agreement with those of the complement fixation test and the rose Bengal plate test. Finally, the specificity of the assay was also evaluated in regard to false-positive serological reactions by using sera from heifers experimentally infected with Yersinia enterocolitica 0:9 (n = 4) and with field sera presenting false-positive reactions (n = 74). The specificity of the cELISA was greater than the specificities of the complement fixation test and the rose Bengal plate test. Indeed, the new assay detected only 31 of the 101 false-positive serum samples detected by at least one serological test.